Scientific Ideas of Moscow Semantic School in China: Borrowing, Adoption and Transformation - L. Guo (Научный диалог)
The article deals with the history and current state of research in Chinese linguistics related to the theoretical ideas of the Moscow Semantic School (MSS). It is noted that this scientific school is one of the most influential theoretical schools of studying semantics in the world. It is reported that the scientific ideas of leading researchers working in line with the MSS has long been recognized and widely used in China, where their distribution took place in three stages: theory borrowing, its adoption and transformation. The system analysis and generalization of features of each of these three stages are presented. The article lists the followers of the Moscow Semantic School in Chinese linguistics and their significant achievements, reveals the current state of research. The ways of spreading the ideas of this school in China are characterized, as well as the problems of its development at the present stage are formulated. It is indicated that the purpose of this article is to develop a useful reference material for the further development of research of theoretical ideas of the Moscow Semantic School in China. The author comes to the conclusion that the studies of the Moscow Semantic School, which are highly appreciated by Chinese linguists, should be used to study and describe the Chinese language.